Narratives in the medicolegal field from the perspective of physicians involved in medical dispute mediation meetings in Taiwan - Chen, Po-Yi; Fu, Chung-Pei; Wang, Chih-Chia (Heliyon, 2023)
Medical treatment and narratives are interrelated. We examined this interrelation by evaluating the medical dispute mediation system in Taiwan. We conducted 16 semi-structured interviews with legal and administrative specialists in medical mediation and physicians involved in mediation meetings. The interview data were reproduced into almost verbatim text for coding and analysis. We examined how narratives were discussed in the field of medicine and identified two approaches to narratives. One was the narrative from a patient's storytelling, that is, narrative-based medicine. The other was the narrative of medical staff, which included shared decision-making and decision aids. Discussions of these approaches revolved around the avoidance of conflicts during medical treatment. However, knowing how to handle unsuccessful medical treatment is crucial. By applying polyphony in narratives, physicians can comprehend the role of narratives in unsuccessful medical treatment, helping themselves to practice how to develop narratives to communicate with patients and their surrogates when encountering any difficulty in different stages of medical treatment.